Peptides actively transported across the tympanic membrane: Functional and structural properties. - Arwa Kurabi; Kerry A Beasley; Lisa Chang; James McCann; Kwang Pak; Allen F Ryan (PLoS ONE)
Otitis media (OM) is the most common infectious disease of children under six, causing more antibiotic prescriptions and surgical procedures than any other pediatric condition. By screening a bacteriophage (phage) library genetically engineered to express random peptides on their surfaces, we discovered unique peptides that actively transport phage particles across the intact tympanic membrane (TM) and into the middle ear (ME). Herein our goals were to characterize the physiochemical peptide features that may underlie trans-TM phage transport; assess morphological and functional effects of phage peptides on the ME and inner ear (IE); and determine whether peptide-bearing phage transmigrate from the ME into the IE. Incubation of five peptide-bearing phage on the TM for over 4hrs resulted in demonstrably superior transport of one peptide, in level and in exponential increase over time. This suggests a preferred peptide motif for TM active transport. Functional and structural comparisons revealed unique features of this peptide: These include a central lysine residue, isoelectric point of 0.0 at physiological pH and a hydrophobic C-terminus. When the optimal peptide was applied to the TM independent of phage, similar transport was observed, indicating that integration into phage is not required. When 109 particles of the four different trans-TM phage were applied directly into the ME, no morphological effects were detected in the ME or IE when compared to saline or wild-type (WT) phage controls. Comparable, reversible hearing loss was observed for saline controls, WT phage and trans-TM peptide phage, suggesting a mild conductive hearing loss due to ME fluid. Perilymph titers after ME incubation established that few copies of trans-TM peptide phage crossed into the IE. The results suggest that, within the parameters tested, trans-TM peptides are safe and could be used as potential agents for noninvasive delivery of drugs, particles and gene therapy vectors to the ME.